Evaluasi Program Pendidikan Kesetaraan Paket B Di Pusat Kegiatan Belajar Masyarakat Al-Kahfi - Asyifa Ervira Masri; Ghina Putri Rusmayadi; Muhammad Praditya Andreansyah; Yogi Maulana Ardika (Peneliti.net, 2022)
Center for Community Learning Activities (PKBM) is an educational institution that was founded by thinking about awareness of the need for community position in the development of non-formal education. The evaluation model used is the Contex-Input-Process-Product (CIPP) evaluation model. The instruments used in the observation were an observation guide, recorded images and sound.